Big data/high performance computing perspectives for unmanned systems - Andresen, Daniel (Kansas State University, 2013)
UAVs have unique information flow requirements from technical and utilitarian perspectives, with the potential for both overwhelming amounts of data and severely limited information flows. When combined with the need for long-term storage and rapid analytical capabilities, the problems can seem intractable. In this talk we will discuss architectural approaches and potential solutions to address these issues from a Big Data/High Performance Computing perspective.
Keywords: Unmanned air vehicles; Data management; Storage; Data analysis